Β-Catenin is required for the differentiation of iNKT2 and iNKT17 cells that augment IL-25-dependent lung inflammation. (December 2015) - Berga-Bolaños, Rosa; Sharma, Archna; Steinke, Farrah; Pyaram, Kalyani; Kim, Yeung-Hyen; Sultana, Dil; Fang, Jessie; Chang, Cheong-Hee; Xue, Hai-Hui; Heller, Nicola; Sen, Jyoti
Abstract Background Invariant Natural Killer T (iNKT) cells have been implicated in lung inflammation in humans and also shown to be a key cell type in inducing allergic lung inflammation in mouse models. iNKT cells differentiate and acquire functional characteristics during development in the thymus. However, the correlation between development of iNKT cells in the thymus and role in lung inflammation remains unknown. In addition, transcriptional control of differentiation of iNKT cells into iNKT cell effector subsets in the thymus during development is also unclear. In this report we show that β-catenin dependent mechanisms direct differentiation of iNKT2 and iNKT17 subsets but not iNKT1 cells. Methods To study the role for β-catenin in lung inflammation we utilize mice with conditional deletion and enforced expression of β-catenin in a well-established mouse model for IL-25-dependen lung inflammation. Results Specifically, we demonstrate that conditional deletion of β-catenin permitted development of mature iNKT1 cells while impeding maturation of iNKT2 and 17 cells. A role for β-catenin expression in promoting iNKT2 and iNKT17 subsets was confirmed when we noted that enforced transgenic expression of β-catenin in iNKT cell precursors enhanced the frequency and number of iNKT2 and iNKT17 cells at the cost of iNKT1 cells. This effect of expression of β-catenin in iNKT cell precursors was cell autonomous. Furthermore, iNKT2 cells acquired greater capability to produce type-2 cytokines when β-catenin expression was enhanced. Discussion This report shows that β-catenin deficiency resulted in a profound decrease in iNKT2 and iNKT17 subsets of iNKT cells whereas iNKT1 cells developed normally. By contrast, enforced expression of β-catenin promoted the development of iNKT2 and iNKT17 cells. It was important to note that the majority of iNKT cells in the thymus of C57BL/6 mice were iNKT1 cells and enforced expression of β-catenin altered the pattern to iNKT2 and iNKT17 cells suggesting that β-catenin may be a major factor in the distinct pathways that critically direct differentiation of iNKT effector subsets. Conclusions Thus, we demonstrate that β-catenin expression in iNKT cell precursors promotes differentiation toward iNKT2 and iNKT17 effector subsets and supports enhanced capacity to produce type 2 and 17 cytokines which in turn augment lung inflammation in mice.